O1-S09.02 HIV elimination without antiretroviral therapy (ART) in Southern India: modelling and projected costs. (10th July 2011) - Pickles, M; Vickerman, P; Vassall, A; Ramesh, BM; Deering, K; Chandrashekar, S; Isac, S; Moses, S; Alary, M; Boily, M C
Abstract : Background: There is widespread interest in the use of antiretroviral therapy for eliminating HIV. However, it is possible that bringing other existing interventions to scale, such as condom promotion among female sex workers (FSWs) could reduce HIV transmission to low levels in some settings. Avahan, the Indian AIDS Initiative, has attained high coverage among FSWs in southern India, achieved large increases in condom use (>90% use condoms consistently), and substantial reductions (35–60% relative decreases over 5 years) in FSW HIV prevalence have been observed in the three districts with three rounds of FSW surveys. This modelling analysis projects the long-term impact of the Avahan intervention strategy in these districts. Methods: A bespoke dynamical model of HIV transmission among FSW/clients was parameterised and fitted to district specific behavioural and STI/HIV prevalence data within a Bayesian framework. The model fits for each district were used to determine whether the long-term impact of the current level of condom use achieved through Avahan, will reduce the HIV incidence among FSWs and clients to less than 1 infection per 1000 FSWs and clients per year (elimination definition used by Granich, Lancet 2009). The probability of local elimination, time till elimination, and costs (extended from detailed costing for first 3 years in 2008 US) and HIV infections averted of achieving this was estimated. Results: With the current high level of condom use in all 3 districts, the probability that the HIV incidence among FSWs and clients becoming <1 infection per 1000 by 2050 is >95%. The Abstract O1-S09.02 figure 1 suggests local elimination is likely to occur earlier in Bellary (median: 2023) than in Mysore (2028) and Belgaum (2030), with the required intervention duration being 11–35 years. The discounted cost of achieving local elimination in each of the settings is estimated to be 8-11 000 000 with 5000–11 000 HIV infections averted up to 2050. Conclusion: Our results suggest Avahan could result in local elimination of HIV among FSWs and clients in these districts without ART. Current discussions around the use of ART for HIV elimination should also consider other prevention strategies, especially in concentrated epidemic settings where eliminating HIV from FSWs and clients is likely to eliminate HIV in the general population. Our modest estimated costs for local elimination could be completely offset against averted ART costs.